Technological Progress in Information and Communication: An Examination of Upcoming Patterns and Prospects - Raj, Sharir (Journal of Advanced Research in Library and Information Science, 2024)
Information and Communication Technology (ICT) has transformed the way we communicate, work, and live. This review article explores recent advancements in ICT, focusing on key trends shaping the landscape of technology-driven innovation. From artificial intelligence (AI) and big data analytics to the Internet of Things (IoT) and 5G connectivity, this paper examines the implications of these developments across various sectors. Additionally, it discusses challenges such as cybersecurity threats and ethical considerations, while also proposing potential solutions to address them. By providing insights into the current state of ICT and its future trajectory, this review aims to inform researchers, practitioners, and policymakers about the opportunities and challenges in this dynamic field. Through an in-depth analysis of emerging technologies and their impact on society, economy, and governance, this article seeks to foster a deeper understanding of the transformative power of ICT and its implications for the future of humanity.